Circulating Long Noncoding RNA TapSAKI Is a Predictor of Mortality in Critically Ill Patients with Acute Kidney Injury. (6th January 2020) - Lorenzen, Johan M; Schauerte, Celina; Kielstein, Jan T; Hübner, Anika; Martino, Filippo; Fiedler, Jan; Gupta, Shashi K; Faulhaber-Walter, Robert; Kumarswamy, Regalla; Hafer, Carsten; Haller, Hermann; Fliser, Danilo; et al.
Abstract: BACKGROUND: Long noncoding RNAs (lncRNAs) are novel intracellular noncoding ribonucleotides regulating gene expression. Intriguingly, these RNA transcripts are detectable and stable in the blood of patients with cancer and cardiovascular disease. We tested whether circulating lncRNAs in plasma of critically ill patients with acute kidney injury (AKI) at inception of renal replacement therapy were deregulated and might predict survival. METHODS: We performed a global lncRNA expression analysis using RNA isolated from plasma of patients with AKI, healthy controls, and ischemic disease controls. This global screen revealed several deregulated lncRNAs in plasma samples of patients with AKI. lncRNA-array–based alterations were confirmed in kidney biopsies of patients as well as in plasma of 109 patients with AKI, 30 age-matched healthy controls, and 30 disease controls by quantitative real-time PCR. RESULTS: Circulating concentrations of the novel intronic antisense lncRNA TrAnscript Predicting Survival in AKI (TapSAKI) ( P < 0.0001) were detectable in kidney biopsies and upregulated in plasma of patients with AKI. Cox regression and Kaplan–Meier curve analysis revealed TapSAKI as an independent predictor of 28-day survival ( P < 0.01). TapSAKI was enriched in tubular epithelial cells subjected to ATP depletion ( P = 0.03). CONCLUSIONS: The alteration of circulating concentrations of lncRNAs in patients with AKI supports TapSAKI as a predictor of mortality in this patient cohort.